Handling qualitative data a practical guide - Richards, Lyn 1944- (SAGE, 2015)
"The third edition of Lyn Richards' best-selling book is the perfect introduction to qualitative research for students and practitioners. Recognizing that for many new researchers dealing with data is the main point of departure, this book helps them to acquire an understanding of the skills and methodological issues that are central to qualitative research. Lyn Richards provides practical guidance on how to handle, reflect on and make sense of rich data, while at the same time showing how a consideration of methods and their philosophical underpinnings informs how we should best handle our data. Detailed sections cover the processes of making, meeting, sorting, coding, documenting and exploring qualitative data. The book shows you how to see a study as a whole and write it up, making and justifying claims from data. Each chapter smoothly integrates software use with discussion of the main challenges that software users are likely to encounter. Novice researchers who use this book will be able to achieve valid and useful outcomes from qualitative analysis, and ensure they do justice to their data. The new edition features: A fully updated website with expanded examples of 'Methods in Practice' where researchers reflect back on their project and what they might have done differently, showing students and practitioners what qualitative data analysis looks like in real life. New critical discussion on the companion website of the contributions of qualitative software and relevance of current software to project tasks. Researchers using different qualitative software packages report how they were used and where there limits were met. Extended coverage within the text of key topics in qualitative research including ethics, reflexivity, and the relationship between research questions and methodological choices. With examples from a wide range of social science disciplines including Education, Media, Sociology, Psychology and Health, this book is the perfect companion for all those starting out qualitative research."--Back cover.